2019
DOI: 10.1128/aac.00618-19
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Food Effect of Tebipenem Pivoxil Hydrobromide after Single and Multiple Ascending Oral Doses in Healthy Adult Subjects

Abstract: Tebipenem pivoxil hydrobromide (TBPM-PI-HBr, formerly SPR994) is an orally available prodrug of tebipenem, a carbapenem with activity versus multidrug-resistant (MDR) Gram-negative pathogens, including quinolone-resistant and extended-spectrum-β-lactamase-producing Enterobacteriaceae. The safety and pharmacokinetics (PK) of tebipenem were studied after administration of single and multiple ascending oral doses of TBPM-PI-HBr in fed and fasted states. Healthy adults received single oral doses of TBPM-PI-HBr at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 5 publications
(6 reference statements)
7
39
1
Order By: Relevance
“…The current work reproduced parameters of T max , C max , AUC 0-∞ , and MRT 0-t previously reported in healthy Chinese or Australian subjects (Eckburg, et al, 2019;Xue, et al, 2019). However, inconsistencies were also noticed; although t 1/2 in our study was close to that in previous report in Chinese volunteers (Xue, et al, 2019), it was observed as 1.0 h in Australian volunteers (Eckburg, et al, 2019).…”
Section: Discussion Pharmacokineticssupporting
confidence: 87%
See 1 more Smart Citation
“…The current work reproduced parameters of T max , C max , AUC 0-∞ , and MRT 0-t previously reported in healthy Chinese or Australian subjects (Eckburg, et al, 2019;Xue, et al, 2019). However, inconsistencies were also noticed; although t 1/2 in our study was close to that in previous report in Chinese volunteers (Xue, et al, 2019), it was observed as 1.0 h in Australian volunteers (Eckburg, et al, 2019).…”
Section: Discussion Pharmacokineticssupporting
confidence: 87%
“…Limited studies aiming at exploring the pharmacokinetics of TBPM have been documented ( Eckburg et al, 2019 ; Nakashima, et al, 2009b ; Xue, et al, 2019 ). These studies provided pharmacokinetic parameters of TBPM either in a single dose or in single gender.…”
Section: Discussionmentioning
confidence: 99%
“…In the Phase 1 SAD/MAD study, TBP-PI-HBr 300 mg and 600 mg administered q8h produced a C max ranging from 6.5-7.8 µg/mL and 13.4 to 15.1 µg/mL, respectively. 15 The supratherapeutic 1200 mg dose used in this study was expected to produce a C max that was 1.3-fold higher and an AUC 0-inf that was 1.8-fold higher than the 600 mg dose. Nine of 24 subjects had C max values greater than the target (at least 1.5fold C max ) with no effect on the QTc interval.…”
Section: Downloaded Frommentioning
confidence: 96%
“…15 Because of short half-life of TBP (<1 h) in humans, no evidence for accumulation was observed with TBP-PI-HBr 600 mg q8h for 14 days. 15 Further, TBP has no active metabolites that could contribute to adverse effects on the QT interval. In the Phase 1 SAD/MAD study, TBP-PI-HBr 300 mg and 600 mg administered q8h produced a C max ranging from 6.5-7.8 µg/mL and 13.4 to 15.1 µg/mL, respectively.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation